Application of Agency Theory in Administrative Accountability and Public Service Delivery in Local Government Councils in Delta State - Egbon, Thomastina Nkechi; Sokoh, Gbosien Chris; Okereka, Onofere Princewill (Universitas Negeri Surabaya, 2023)
The Agency Theory was extensively covered in this study. The investigation used secondary data from books and articles that had already been published. Despite objections, changes in the government, and reservations from some sections of the public, the agency theory has proven to be a useful paradigm in enhancing public accountability and improving the delivery of public services. Local government councils in Delta State may benefit from applying agency theory, which can enhance the provision of public services, employee performance, administrative accountability in the public sector, and public confidence in elected officials. The majority of public administration research reflects agent theory-related presumptions that support public administrators' capacity for learning and effectiveness. As a result of the aforementioned, it is crucial for Delta State's local government council leaders to strictly adhere to accountability in the management of local government affairs in order to encourage quality service delivery. The study comes to the conclusion that in Nigerian public administration, administrative accountability is a crucial but underdeveloped concept. The phrase is freely used by academics and professionals to refer to accountability for one's actions or behavior. Administrators and organizations are responsible in the sense that they must account for their actions. Beyond this fundamental idea of answerability, the term has not undergone much development in Delta State's local government councils.